(untitled) (Malaysian Journal of Fundamental and Applied Sciences, 2017)
In the middle of the era of technology and fast-growing industry nowadays, biodiesel (methyl ester) has been identified as a sustainable fuel to replace petroleum. Hence, the separation and purification of the methyl ester after the trans-esterification process is essential since the purification of methyl ester is compulsory for the fuel industry in order to fulfill the strict global standard particulars for methyl ester. One of the current method used for separation and purification of methyl ester is called wet washing technology. However, this technology has its own drawbacks such as huge amount of water consumption as well as high cost for the wastewater treatment process. Due to these drawbacks, fractional crystallization process is proposed in order to save water and minimize the time consumed for the process of separation and purification of methyl ester. Fractional crystallization is a process that involved a solid-liquid separation where the process takes place in a crystallizer. In this process, methyl ester was separated from the glycerol based on their differences in term of melting point of the components. By observing the layer formation of the components, the effect of cooling time and coolant temperature on the performance of separation and purification of methyl ester by fractional crystallization process were studied. The purified methyl ester obtained was placed in a gas chromatographer in order to test the purity of methyl ester and to evaluate the efficiency of the process based on two parameters that has been investigated which are effective partition constant (K) and concentration efficiency (Eff). It was found that to achieve highest effectiveness of fractional crystallization system and highest concentration efficiency where K and Eff are 0.51 and 47.71%, respectively, the fractional crystallization must operate at coolant temperature range of -10 to -12ºC and cooling time range of 30 to 35 minutes.